Online al-da'wah al-fardiyyah in e-group : a study on islah.net - Muhamad Faisal Ashaari (Kulliyyah of Islamic Revealed Knowledge And Human Sciences, International Islamic University Malaysia, 2014)
The emergence of communication-mediated communication (CMC) in the online environment has presented a great potential for Muslims to diversify their efforts of al-dacwah. Noted of the diversity of the internet users, these efforts should be confined to a particular individual or to a specific type of people who engage in online communication due to the sharing of some similar backgrounds and interests. This approach suite the concept of al-dacwah al-fardiyyah, a typical approach of al-dacwah addressed exclusively to an individual or a small group of people. This study means to examine the feasibility of online al-dacwah al-fardiyyah in e-group through three elements namely viability, sociability and competency. Islah.net is taken as the case study to investigate the ways of al-dacwah presented in this e-group. In conducting the studies, a model of online al-dacwah has been developed, adopting and adapting from two models of online learning; “e-moderation” and community of inquiry (CoI). The model consists of three domains, namely viability, sociability and competency. This is a qualitative study that employs content analysis and interview as the methods of the study. The content analysis is carried out to the selected messages of Islah.net and the interview is conducted with seven members and a moderator of Islah.net. The results show that al-dacwah is viable in Islah.net. The analysis indicates that the dissemination constitutes 40%, while participation consists of 48.1% and mobilisation only gets 4.1% of the whole messages in Islah.net in the selected months under the study. However, it is subjected to three circumstances, namely the objective of the formation of an online group discussion, the number of members in the group, and the topic of discussion. Next, the study discovers that the sociability is less shown in Islah.net in which the affective expression consists of 4.6 % messages while group cohesion has 6.8% and open communication comprises of 3.5% messages. Finally, the study shows that Islah.net is not adequately competent in achieving the objective of al-dacwah because the messages that contain the indication of competency make only 10.9%. These results support that the concept of “narrowness” of the target group in online al-dacwah is not totally similar to the original concept of al-dacwah al-fardiyyah due to different environments. Therefore, to achieve the level of quality friendship the online medium should be combined together with the face-to-face communication.